2016
DOI: 10.1016/j.powtec.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of a powdery spinel-type Li+ ion sieve derived from biogenic manganese oxide in alginate beads

Abstract: A powdery lithium ion sieve (HMO) derived from biogenic birnessite was homogeneously integrated in sodium alginate (AL) beads. The composite beads were then characterized and their Li + adsorption properties were investigated. Scanning electron microscopy-energy dispersive spectroscopy analysis showed that the HMO particles were homogeneously dispersed in the AL beads even after drying. The adsorption isotherm of Li + adsorption to HMO encapsulated in AL beads (HMO-AL) was well fitted by the linear Langmuir mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…11−15 Not only synthetic polymeric materials but also natural material derived binders have been also investigated for granulation of HMO. 16,17 Ma et al synthesized HMO foam by using pitch as binding material and polyurethane as template. 17 Unfortunately, these binding materials tend to block HMO and interfere with seawater diffusion, thereby decreasing the Li adsorption performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11−15 Not only synthetic polymeric materials but also natural material derived binders have been also investigated for granulation of HMO. 16,17 Ma et al synthesized HMO foam by using pitch as binding material and polyurethane as template. 17 Unfortunately, these binding materials tend to block HMO and interfere with seawater diffusion, thereby decreasing the Li adsorption performance.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of polymeric materials, such as polyvinyl chloride (PVC), poly­(vinyl alcohol) (PVA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), and polyacrylamide (PAM), have been used as binding materials for HMO granulation. Not only synthetic polymeric materials but also natural material derived binders have been also investigated for granulation of HMO. , Ma et al synthesized HMO foam by using pitch as binding material and polyurethane as template . Unfortunately, these binding materials tend to block HMO and interfere with seawater diffusion, thereby decreasing the Li adsorption performance.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to several reports on the use of organic and inorganic materials as binders for the granulation of metal-based LISs, reports on the use of biopolymers as binders are limited in the open literature (cf. Figure 4) [24,[49][50][51][52][53][54][71][72][73][74][75][76][77][78][79]. Additionally, there are currently no review articles that highlight the available knowledge gaps on the use of biopolymers as binders for the granulation of LISs.…”
Section: Granulation Of Liss Using Inorganic Materialsmentioning
confidence: 99%
“…Additionally, there are currently no review articles that highlight the available knowledge gaps on the use of biopolymers as binders for the granulation of LISs. Most recent studies have focused on the use of chitosan, alginate, agar, and cellulose as binders to prepare granulated LISs [24,[49][50][51][52][53][54][71][72][73][74][75][76][77][78][79]. For instance, numerous studies [49][50][51][52][53] have reported on the use of chitosan in various forms (cross-linked and non-cross-linked) as binder for the granulation of LISs.…”
Section: Granulation Of Liss Using Inorganic Materialsmentioning
confidence: 99%
“…Lithium and its compounds are widely used in many fields, especially in Li‐ion battery, electric vehicles and portable electronic device, which decides the surging requirement of lithium resources annually . Various techniques such as liquid‐liquid extraction, precipitation, ion exchange, membrane process, desalination and adsorption have been reported for separation and purification of lithium from mines and Salt Lake brines . Among these methods, adsorption is an ideal and the most promising method compared to other techniques due to the low concentration of lithium in local brines, convenience of operation, lower cost, efficient, recyclable and being a relatively more environment friendly process .…”
Section: Introductionmentioning
confidence: 99%